Factors Associated With Childhood Asthma and Wheeze in Chinese Preschool-Aged Children - Deng, Xiangling; Yang, Min; Wang, Shunan; Wang, Qiong; Pang, Bo; Wang, Kundi; Zhang, Zhixin; Niu, Wenquan (Frontiers in Medicine, 2021)
This study was prepared to identify and characterize potential factors associated with childhood asthma and wheeze in Chinese preschool-aged children. A comprehensive questionnaire was designed for children aged 3-6 years and their parents or guardians in Beijing and Tangshan from September to December 2020. The least absolute shrinkage and selection operator (LASSO) model was used to identify factors in significant association with childhood asthma and wheeze, respectively. The LASSO model was internally validated using bootstrap resampling with 100 replications. A total of 9529 questionnaires were certified as eligible for inclusion after stringent quality control. The prevalence of doctor-diagnosed childhood asthma and parent-reported wheeze was 2.8% and 6.2%, respectively. Factors simultaneously associated with childhood asthma and wheeze were children’s history of allergic rhinitis, hayfever, eczema, initial age of using antibiotics, body mass index category, and family history of asthma. Specifically, children’s vitamin D supplement duration was significantly associated with childhood asthma, whereas assocaition with childhood wheeze was significant for intake frequency of children’s night meals and screen time. Modeling of significant factors in nomograms had decent prediction accuracies, with C-index reaching 0.728 and 0.707 for asthma and wheeze, respectively. In addition, internal validation was good, with bootstrap C-statistic of being 0.736 for asthma and 0.708 for wheeze. Taken together, our findings indicated that the development of asthma and wheeze among preschool-aged children was probably determined by the joint contribution of multiple factors including inherited, nutritional, unhealthy lifestyles, and history of allergic disease. Further validation in other groups is necessary.